An analytical analysis of the commercial geography of India and its key agro-based industries (International Journal of Food and Nutritional Sciences, 2022)
AbstractValue is increased by agro-processing since the raw resources are transformed into finished consumer items or intermediate goods. There is a wide spectrum of value addition procedures, from basic preservation to the creation of high-value goods. Population growth, increased urbanisation, and changing dietary preferences have all contributed to a rise in the demand for processed foods in recent years. Therefore, the agro-processing sectors have great potential to stimulate economic growth. The agro-processing industry's multiplier effect may have a significant impact on a country's economic growth. When the potential of the complete commodities system's processing options is considered, the possibilities explode. Paddy, straw, husk, bran, and rice kernel are all byproducts of the paddy plant, which a farmer can grow on his land. As a result, a complex of processing businesses (rice mills, solvent extraction plant for rice bran oil, processing of husk for variety of goods, and straw paper/board mills) may be supported by the output of paddy with an initial investment for cultivating paddy. The processing of raw commodities like meat, bones, leather, skins, wools, etc. derived from animals provide similar opportunities for value addition. Opportunities abound in India for businesses that handle agricultural goods such grains, fruits, vegetables, meat, and fish. This potential is, however, seldom used. Because of this, doing the research is crucial.